For investigate the role of ultrasound and platelets count as an important marker for the diagnosis and prognosis of dengue patients - ., Sunaina; Desai, Vishal K.; Saini, Rahul; Arora, Rashmi (International Journal of Research in Medical Sciences, 2018)
Background: Dengue is although self limiting viral disease but if severe complications take place than it becomes lethal. Plasma leakage is main pathology which results in fluid deposits in various organs. This plasma leakage is related to platelet count. Most important thing in treating dengue patient is to know the complications at the earliest. And ultrasound is the most sensitive and easily approachable, cost effective investigation for detecting the complications. Methods: This cross-sectional observational pilot study was carried out in the department of radiodiagnosis, pandit bhagwat dayal Sharma institute of medical sciences, Rohtak. One hundred and two patients with serologically confirmed dengue fever were included in this study. Ultrasound examinations were carried out by ultrasound machine with 5-13 MHZ probe by radiologists. Abdomen and thorax scanning were done thoroughly. Important findings like Gall bladder thickening hepatomegaly, splenomegaly, free fluid which are pathological markers for dengue were specially seen. Then these findings are relate to the age group and platelet count. Results: By applying chi square test we found that there is statistically difference in number of patients in age group 16-30 yrs having gall bladder wall thickening, hepatomegaly, free fluid, splenomegaly and pleural effusion as compared to other age groups (p<0.05) an also in patients having less than 20,000 platelets, only gall bladder thickening, ascites and hepatomegaly were statistically more significant as compared to other groups having more number of platelets (p<0.05). Conclusions: So, ultrasound and platelet count are important markers for diagnosis and prognosis of dengue patients. Ultrasound and Platelets count are important markers for the diagnosis as well as prognosis of dengue patients.